Drunk and Delirious Defences: Intoxication and Insanity in the Criminal Code (WA) - Mullins, Gemma (Curtin University, 2017)
In State of Western Australia v Herbert [2017] WASC 101, the question whether s 28(2) of the Criminal Code (WA) (‘Code’) disentitles a concurrently insane and intoxicated accused from availing himself of the insanity defence arose for the first time in this jurisdiction. Critically, the current interpretation of the interaction between the insanity and intoxication defences in ss 27-28 of the Code disentitles an intoxicated accused from availing himself of the insanity defence irrespective of whether his intoxication had any connection to his loss of capacity. This thesis analyses the interaction between the insanity and intoxication defences and suggests how those sections should be interpreted and operate. To that end, it seeks to address how the law should respond to cases such as Herbert where there is an operative mental impairment in circumstances where the accused is also intoxicated, in particular, in circumstances where intoxication is not necessarily connected to a loss of capacity.